2014
DOI: 10.1186/1471-2156-15-27
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association and systems genetic analyses of residual feed intake, daily feed consumption, backfat and weight gain in pigs

Abstract: BackgroundFeed efficiency is one of the major components determining costs of animal production. Residual feed intake (RFI) is defined as the difference between the observed and the expected feed intake given a certain production. Residual feed intake 1 (RFI1) was calculated based on regression of individual daily feed intake (DFI) on initial test weight and average daily gain. Residual feed intake 2 (RFI2) was as RFI1 except it was also regressed with respect to backfat (BF). It has been shown to be a sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 70 publications
5
103
0
Order By: Relevance
“…In contrast to previous RFI studies (Young et al, 2011;Mani et al, 2013;Montagne et al, 2014) backfat was not included in the model in this study. However, Do et al (2014) established a correlation coefficient of 0.96 between models with or without backfat, suggesting that the non-inclusion of backfat in this study will not unduly influence the results.…”
Section: Resultsmentioning
confidence: 66%
“…In contrast to previous RFI studies (Young et al, 2011;Mani et al, 2013;Montagne et al, 2014) backfat was not included in the model in this study. However, Do et al (2014) established a correlation coefficient of 0.96 between models with or without backfat, suggesting that the non-inclusion of backfat in this study will not unduly influence the results.…”
Section: Resultsmentioning
confidence: 66%
“…A recent study on LD structure by Villa-Angulo et al (2009) revealed that there were regions of high LD extending up to 100 kb and the size of haplotype blocks ranged between 30 bases and 75 kb (the average being 10.3 kb). Previous studies also suggested that a similar distance could be used in the SG approach to capture the causal genes/SNPs affecting a quantitative trait like feed efficiency (Do et al, 2014). The over-representation analyses identified five KEGG pathways associated with feed efficiency-related traits (Table 3).…”
Section: Systems Geneticsmentioning
confidence: 99%
“…Compared with traditional QTL mapping strategies, GWAS confers major advantages in the power to detect variants and is a powerful tool to analyse the genetic architecture of important animal characteristics (Hirschhorn and Daly 2005;Kronenberg 2008). So far, many QTL, genomic regions, and SNPs have been identified in various farm animals, such as cattle (Bolormaa et al 2010;Sherman et al 2010), pigs (Do et al 2014;Zhang et al 2016) and poultry Yuan et al 2015). So, it is necessary to use GWAS to study the small intestine length in chickens.…”
Section: Introductionmentioning
confidence: 99%